(untitled) (Bangladesh Journal of Microbiology, 2016)
Two ethanol fermenting Saccharomyces cerevisiae were isolated from date juice and grapes and grown in YEPD medium. They were characterized for alcoholic fermentation using sugarcane molasses and their growth conditions were optimized with respect to pH and sugar concentration. Results revealed a temperature of 30ºC, pH 6.0 and 6.5% sugar concentration as optimum for fermentation. Stress tolerance tests showed that date juice isolate was highly tolerant to temperature, pH and high ethanol concentration in the medium. Under optimized conditions, S. cerevisiae isolated from date-juice produced 7.75% of ethanol in molasses as estimated by Conway method. Bangladesh J Microbiol, Volume 30, Number 1-2,June-Dec 2013, pp 49-54